Confidences : Parce que c'était lui, parce que c'était moi. - Lunghi, Enrico; Jean, Marie-Josée; Berecz, Agnes; Hamidi, Soraya; Philippi, Desa; Samore, Sam; Casino Luxembourg - Forum d'Art Contemporain Luxembourg (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain, 2001)
Aberg, Charlotte ; Bay, Didier ; Brotherus, Eline ; Caron, Nathalie ; Guilbert, Charles ; Cumming, Donigan ; Delvoye, Wim ; Drescher, Doris ; Dubois, Jean ; Hatoum, Mona ; Hollywood, Annette ; Laliberté, Sylvie ; Letinsky, Laura ; Németh, Hajnal ; Rist, Pipilotti ; Wearing, Gillian
Casino Luxembourg - Forum d'art contemporain, Luxembourg, 12.05 - 15.07.2001
kunstcatalogus